The design of team formation system - a coordination with the perspectives of Delone and Mclean IS success model / Safura Adeela Sukiman and Puteri Nur Hidayah Kamaludin - Sukiman, Safura Adeela; Kamaludin, Puteri Nur Hidayah (UiTM Press, 2020)
Instructors must constantly think of more innovative teaching and learning techniques to ensure that the graduates they produce are in line with the changing needs of the industry. One such technique is project- based learning; the learning technique in which students are divided into smaller teams. From previous researches, team formation using personality traits was seen as more appropriate to form an ideal and balanced team. To do so, students must answer questions that will be analysed and based on the analysis, their personality traits are identified and incorporated into teams of various deal personality traits. Problem occurs as this process is seen as a daunting task for the instructors.